2011
DOI: 10.1075/sl.35.1.10sim
|View full text |Cite
|
Sign up to set email alerts
|

Bare classifiers and definiteness

Abstract: In some (numeral) classifier languages, a classifier may occur “bare” (i.e. with a noun but without a numeral) and the nominal expression receives a definite interpretation. On the basis of evidence from Cantonese and Mandarin Chinese, Cheng and Sybesma (1999) hypothesize that classifier languages exhibit either the bare classifier or the bare noun pattern for definite reference, but not both. To evaluate this hypothesis against more typologically diverse languages, a parallel elicitation study of three non-Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 0 publications
0
23
0
Order By: Relevance
“…There is ample evidence for the need for both a [ specific ] feature and a [ definite ] feature. This evidence comes from the crosslinguistic behavior and distribution of determiners and classifiers (Haspelmath , Lyons , Cowper & Hall , Ionin , Simpson, Soh & Nomoto , Cowper & Hall ); the features of indefinite pronouns (Fodor & Sag , von Heusinger ); nonscopal specific interpretations of indefinites (Fodor & Sag , von Heusinger ); and patterns of acquisition of determiners in second‐language acquisition (Ionin, Ko & Wexler , Ionin, Zubizarreta & Philippov ). There is also ample evidence for features like [ human ] and [ animate ], for example, from verbal marking in Algonquian languages (Piggott , Wiltschko & Ritter , among others); verbal prefixes in Abkhaz (Hewitt , cited by Mithun ); nominal marking in Selayarese (Finer ); and impersonal pronouns crosslinguistically (Sigurðsson & Egerland , Fenger ).…”
Section: Proposalmentioning
confidence: 99%
“…There is ample evidence for the need for both a [ specific ] feature and a [ definite ] feature. This evidence comes from the crosslinguistic behavior and distribution of determiners and classifiers (Haspelmath , Lyons , Cowper & Hall , Ionin , Simpson, Soh & Nomoto , Cowper & Hall ); the features of indefinite pronouns (Fodor & Sag , von Heusinger ); nonscopal specific interpretations of indefinites (Fodor & Sag , von Heusinger ); and patterns of acquisition of determiners in second‐language acquisition (Ionin, Ko & Wexler , Ionin, Zubizarreta & Philippov ). There is also ample evidence for features like [ human ] and [ animate ], for example, from verbal marking in Algonquian languages (Piggott , Wiltschko & Ritter , among others); verbal prefixes in Abkhaz (Hewitt , cited by Mithun ); nominal marking in Selayarese (Finer ); and impersonal pronouns crosslinguistically (Sigurðsson & Egerland , Fenger ).…”
Section: Proposalmentioning
confidence: 99%
“…[bare N] dinosaur extinct past "Dinosaurs are extinct." (Krifka 1995) Turning to other classifier languages, many authors have observed that they employ various strategies to express definiteness and indefiniteness (Bhattacharya 1999;Sybesma 1999, 2005;Dayal 2011bDayal , 2012aJenks 2011;Kookiattikoon 2001;Li 2011;Liu 2010;Nguyen 2004;Simpson 2005;Simpson et al 2011;Sio and Sybesma 2008;Trihn 2011;Jiang 2012, a.o. ;Yang 2001).…”
Section: How Do Classifier Languages Without D Manage?mentioning
confidence: 99%
“…Below, we present two generalizations concerning bare classifier phrases and numeral classifier phrases based on the table in 12 14, allow bare classifier phrases in only one position with only one interpretation; some languages, such as Cantonese (15), freely allow them to appear in both subject and object positions with different interpretations.10 13 The dog likes to eat meat." (Cheng and Sybesma 1999) The second generalization concerns numeral classifier phrases: all languages have the indefinite use of numeral classifier phrases (16-19), but only some languages, such as Vietnamese and Thai (17), allow 9 Sybesma (1999, 2005) claim that in Cantonese bare nouns are unable to express definiteness, but Wu and Bodomo (2009) and Simpson et al (2011) show that if a certain context is provided, bare nouns in Cantonese can be read as definite. Regarding bare nouns in Vietnamese, Nguyen (2004: 1-2) claims that they can be interpreted as definite, but Trihn (2011) claims that they cannot be definite.…”
Section: How Do Classifier Languages Without D Manage?mentioning
confidence: 99%
See 1 more Smart Citation
“…Important references for Bangla classifiers include Dasgupta (1983Dasgupta ( , 1985, Bhattacharya (1999aBhattacharya ( , 1999b, Dasgupta and Bhattacharya (1993) and Ghosh (2001). For more recent work on the topic, see Simpson et al (2011), Chacón (2011, Biswas (2011Biswas ( , 2013 and Jiang (2012),, most of which appeared after the first draft of the present paper had been written. I have therefore been unable to fully incorporate insights from them.…”
mentioning
confidence: 99%